2017
DOI: 10.3322/caac.21405
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and adverse breast cancer risk and outcome: Mechanistic insights and strategies for intervention

Abstract: Recent decades have seen an unprecedented rise in obesity and the health impact thereof is increasingly evident. In 2014, worldwide more than 1.9 billion adults were overweight (BMI 25–29.9kg/m2) and of these over 600 million were obese (BMI≥30kg/m2). While the association between obesity and risk of diabetes and coronary artery disease is widely known, the impact of obesity on cancer incidence, morbidity and mortality is not fully appreciated. Obesity is associated with a higher risk of developing breast canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
637
3
38

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 697 publications
(696 citation statements)
references
References 207 publications
(406 reference statements)
18
637
3
38
Order By: Relevance
“…Another classic risk factor for the diagnosis of breast cancer is overweight (including obesity) [30,31], and the present data corroborates this assertion. A study among survivors also observed a high prevalence of overweight status in 154 patients from a reference center in Brazil [32].…”
Section: Discussionsupporting
confidence: 88%
“…Another classic risk factor for the diagnosis of breast cancer is overweight (including obesity) [30,31], and the present data corroborates this assertion. A study among survivors also observed a high prevalence of overweight status in 154 patients from a reference center in Brazil [32].…”
Section: Discussionsupporting
confidence: 88%
“…In an observational prospective study consisting of about 350,000 US women, higher BMI was very significantly associated with increased risk of death from breast cancer [6]. Although the impact of obesity on diabetes and heart disease is well known, its effect on cancer remains largely unexplored in clinical practice [7, 8]. …”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, fat tissue shows increased levels of leptin, resulting in low TGF‐β and IL‐10 levels. However, obese breast cancer patients still have higher mortality, which may be a result of the association between obesity and increased tumor size, positive lymph node involvement, and triple‐negative subtype, but not the secretion of TGF‐β and IL‐10 . Other nutritional parameters were not significantly associated with levels of TGF‐β, IL‐10 and Foxp3, potentially because there is a nondirect correlation between them in terms of biological mechanism.…”
Section: Discussionmentioning
confidence: 94%